PENGARUH RANGE OF MOTION EXERCISE TERHADAP KEKUATAN OTOT PADA PASIEN STROKE DI WILAYAH PUSKESMAS SIDOTOPO SURABAYA - Kristiani, Rina Budi (JURNAL NERS LENTERA, 2017)
The weakness muscle is the biggest impact on patients with stroke, to the practice Range of Motion Exercise with the aim is to maintain or preserve muscle strength, to maintain mobility joints and simulate circulation. With an increase in the incidence of stroke and disability, if the practice Range of Motion Exercise is not implemented it will be a significant decrease in muscle strength, cause muscle kontraktur and a decubitus. The study aims to find his Range of Motion Exercise of muscle strength in patients with stroke in the Puskesmas Sidotopo Surabaya. This study uses Pra-Eksperimental One-Group Pra-Post Test Design. Population in this study is a stroke patient who live in the Puskesmas Sidotopo Surabaya and sampels 32 of responden. The sample by using techniques purposive sampling. Variables independent in this study is Range of Motion Exercise and the variables dependent is muscle strength. The intstrumen used in the collection of data is an observation to the strength of muscles. The results showed an increase in strength of muscle strength from scale 3 to scale 4 and from scale 4 to scale 5 after the Range of Motion Exercise. The t-test statistic test shows that p value 0.000 (α